Action! : how movies began - McCarthy, Meghan (Simon & Schuster Books for Young Readers, 2022)
Presents a nonfiction picture book that tells the story of how movies came to be, beginning with early photography experimentation by English photographer Eadweard Muybridge and French scientist Étienne-Jules Marey, and the work of American inventor Thomas Edison, whose team developed the first motion picture machine. Chronicles technical advancements made by various inventors that have led to some of the most famous films in history. Also discusses discrimination against Black performers. Includes back matter with additional information.